Experiencias socioemocionales de docentes relacionados con educación inclusiva en un instituto educativo de Uribia, departamento de la Guajira. (2023)
This study proposes to identify and describe socio-emotional experiences that teachers have regarding the inclusion of early childhood children. For this, it has a qualitative method of descriptive scope and phenomenological design, it is carried out with a sample of 4 primary school teachers, three women and one man from the Juyasirain Educational Institute of Uribía, department of La Guajira.